2020
DOI: 10.33963/kp.15048
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon versus radiofrequency ablation for persistent atrial fibrillation: a systematic review and meta‑analysis

Abstract: BACKGROUND Clinical outcomes of catheter ablation for persistent atrial fibrillation (AF) remain discouraging. AIMS This meta-analysis aimed to compare cryoballoon ablation (CBA) with radiofrequency ablation (RFA) for persistent AF. METHODS A systematic search of the PubMed, EMBASE, and Cochrane Library databases was performed for studies comparing the outcomes between CBA and RFA. Seven trials including 934 patients were analyzed. RESULTS There were no differences between groups in terms of freedom from atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Both CB and RF ablation techniques are considered as standard methods with similar outcomes. However, based on the largest comparison of both techniques -the "Fire and Ice study" -patients after CB ablation had significantly fewer all-cause re-hospitalizations, cardiovascular re-hospitalizations, re-ablations, and direct current cardioversions after the index procedure [2,16,24,25]. In our opinion there are several important advantages of CB ablation making it the preferred approach.…”
Section: Acute and Long-term Outcomementioning
confidence: 87%
“…Both CB and RF ablation techniques are considered as standard methods with similar outcomes. However, based on the largest comparison of both techniques -the "Fire and Ice study" -patients after CB ablation had significantly fewer all-cause re-hospitalizations, cardiovascular re-hospitalizations, re-ablations, and direct current cardioversions after the index procedure [2,16,24,25]. In our opinion there are several important advantages of CB ablation making it the preferred approach.…”
Section: Acute and Long-term Outcomementioning
confidence: 87%
“…A retrospective analysis of 678 patients from AXAFA-AFNET 5 trial showed that ER occurrence is not associated to energy source applied 5 and a recent meta-analysis proves that arrhythmia relapse during BP does not differ in RFA-and CBAtreated patients (relative risk: 0.73; 95% CI: 0.50-1.06; p = .1). 41 All the aforementioned data highlight that irrespective of energy source, early arrhythmia recurrence is correlated with poor arrhythmia-free survival in the long term.…”
Section: Discussionmentioning
confidence: 98%
“…Contemporary meta-analytic studies have sought to assess the comparative efficacy of RF and CB ablation for AF [21][22][23]; however, these analyses included mixed AF types and/or generations of ablation technologies, precluding comparison of the latest generations of RF and CB technologies available for the treatment of PsAF. A meta-analysis by Liu and colleagues [23] is the first to compare the efficacy and safety of cryoablation and RF ablation in PsAF ablation. The analysis found that there was no difference in terms of freedom from atrial arrhythmia between cryoablation and RF ablation (RR 1.04; 95% CI 0.93-1.15; P = 0.52) [23].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Liu and colleagues [23] is the first to compare the efficacy and safety of cryoablation and RF ablation in PsAF ablation. The analysis found that there was no difference in terms of freedom from atrial arrhythmia between cryoablation and RF ablation (RR 1.04; 95% CI 0.93-1.15; P = 0.52) [23]. Importantly, studies included in the analysis differed with respect to study design, intervention (i.e., mixed generation and/or type of catheter), and ablation strategy (i.e., PVI alone, PVI plus additional ablations).…”
Section: Discussionmentioning
confidence: 99%